KONDISI SOSIAL EKONOMI DAN KESEHATAN MASYARAKAT KAMPUNG PUNAN MALINAU KABUPATEN BERAU DENGAN KEBERADAAN BEBERAPA PERUSAHAAN SAWIT - Sri Ngapiyatun; Sri Hartini; Humairo Aziza; Wartomo Wartomo; Sukariyan Sukariyan; Rossy Mirasari; Rusli Anwar (JURNAL AGRIMENT, 2021)
This research background with a lot of oil companies that thrive in Kampung Punan Malinau it could be an impact on changes in socioeconomic conditions and public health, for the study aims to determine the interaction social, education, income, accessibility, and health.Based on the results of this study it can be concluded that the work of the people of Punan Malinau Village who used to be farming, now there is progress working in oil palm companies in the Punan Malinau Village area. The presence of companies economically also has a positive impact on the development of alternative sources of livelihood, namely the recruitment of local workers in companies and access to marketing of agricultural products that are well developed.Meanwhile, in terms of public income before the company existed it was only under Rp. 1,000,000, - but after the existence of the oil palm company, the income has increased, namely Rp. 4,000,000 to Rp. 5,000,000 and more are supported by their personal income, namely private oil palm plantations that can reach Rp. 16,000,000 and more per month.